Фібули з Тіри (знахідки 1996—2010 рр.) - Савельєв, О.К. (Археологія, 2013)
Розкопки останніх років у Тірі не тільки значно збільшили колекцію фібул, а й поповнили її невідомими досі зразками. Публикуется коллекция фибул из Тиры, полученная в ходе полевых исследований 1996—2010 гг. Она состоит из 50 целых и фрагментированных фибул. Как правило, фибулы происходят из смешанных слоёв, только единичные застежки были найдены в слоях, не нарушенных поздними вторжениями. Часть из них представляют случайные находки. Фибули хранятся в фондах Одесского археологического музея и Белгород- Днестровского краеведческого музея.
В результате археологических работ последних лет на тирском городище были открыты слои эллинистического времени, которые содержали несколько фибул этого времени. Впервые выделена группа латенских застежек, не известных здесь ранее. В сочетании с другими находками латенских типов они позволяют несколько скорректировать наши представления не только об истории Тиры в позднеэллинистическое время, но также о ее культурных связях с окружающим миром.
Пока несколько проблематичным остается четкое выделение фибул середины I в. до н. э. — середины I в. н. э.
Собрание фибул римского времени также дополнилось новыми типами. Анализ коллекции показал, что в I — середине III вв. н. э. в Тире превалировали фибулы причерноморских и провинциально-римских типов. После выхода римского гарнизона из Тиры их количество сокращается, и со второй половины III в. начинают преобладать фибулы черняховского типа, которые вместе с «воинскими» фибулами известны здесь и в IV в. н. э. Published in the article is the collection of fibulae from tyras obtained during the field research from 1996 to 2010. the collection includes 50 intact and fragmented fibulae. As a rule, they originate from mixed layers and only several buckles were found in layers not disturbed by the later intrusions. Some of them are occasional finds. the fibulae are kept in funds of the odesa Archaeological Museum and the Bilhorod-Dnistrovskyi local lore Museum.
Hellenistic period layers containing several fibulae of this time were revealed at the tyras hill-fort by the recent years archaeological research. the group of la tene fasteners not known here before was distinguished here for the first time. together with other finds of la tene type they allow correcting in some way our knowledge not only in the late Hellenistic history of tyras, but also in its cultural relations with outward world.
It is still to some extent problematic to distinguish clearly the fibulae of the period from the middle 1st c. BC to the middle 1st c. AD.
the roman period fibulae collection was also complemented by the new types. the collection analysis showed that the Black Sea north and the Provincial roman types fibulae prevailed in tyras from the 1st c. to the middle 3rd c. AD. their number has decreased after the roman garrison left tyras, and the Cherniakhiv type fibulae become prevailing since the second half of the 3rd c., together with «military» fibulae they are known here also in the 4th c. AD.